Memantine Differentially Regulates Tau Phosphorylation Induced by Chronic Restraint Stress of Varying Duration in Mice - Yunsheng Liu; Lan Cao; Xiaoxu Zhang; Yan Liang; Yuxia Xu; Cuiqing Zhu (Neural Plasticity)
Exposure to chronic psychiatric stress has been linked to Alzheimer’s disease-related tau hyperphosphorylation and abnormalities in glutamate neurotransmission. However, the pathological relationship between glutamatergic dysfunction and tau phosphorylation in the cerebral cortex under chronic psychiatric stress is not fully understood. The present study investigated the effects of memantine (MEM, 5 and 10 mg/kg), an uncompetitive N-methyl-D-aspartate (NMDA) receptor antagonist, on chronic restraint stress- (CRS-) induced tau phosphorylation in mice. CRS administered for 16 or 28 consecutive days (1 h daily) induced significant tau phosphorylation in the brain. MEM treatment suppressed the elevation of phosphorylated tau (P-tau) levels induced by 16-day CRS in a dose-dependent manner. P-tau reduction was accompanied by the attenuation of the upregulation of GSK3β and CDK5 expression and the downregulation of PP2A activity induced by CRS. Additionally, MEM reduced CRS-induced upregulation of NMDA receptor subunit levels (GluN2A, GluN2B) in the frontal cortex. However, MEM markedly enhanced tau phosphorylation in the frontal cortex and other cerebral cortical regions following 28 days of CRS. The stimulatory effect of MEM on CRS-induced tau phosphorylation was correlated with increased activities of AKT, JNK, and GSK3β, inactivation of PP2A, and downregulation of Pin1 and HSP70. Moreover, MEM did not effectively reverse the NMDA receptor upregulation induced by 28-day CRS and even increased GluN2B subunit levels. In contrast to the duration-dependent effects of MEM on P-tau levels, MEM produced an anxiolytic effect in both regimens as revealed by elevated plus maze testing. However, MEM did not affect the body weight reduction induced by CRS. Thus, MEM exerts distinctive effects on CRS-induced tau phosphorylation, which might be related to the expression of GluN2B. The differential effects of MEM on P-tau levels have crucial implications for its clinical application.